Organizacja i działalność służb zaopatrzeniowych w Łódzkim Okręgu Wojskowym w latach 1945–1946 - Jarno, Witold (Acta Universitatis Lodziensis. Folia Historica, 2013)
The article describes the organization and activity several services, whose task it was the supply all the military units stationed in the Lodz Military District in years 1945–1946. Described quartermaster services were responsible for the current supply troops with food, uniforms, equipment, buildings and barracks, fuel, water and many other useful things. The construction service was responsible for the living conditions of the soldiers in the barracks and the technical condition all military facilities. The service weapon was responsible for the supply of arms and ammunition, weapons maintenance and ensuring right conditions of storage. Because of development of motorization, a very important also was the automotive service, which supplied military vehicles, lubricants, fuel and spare parts necessary for the efficient users of all the military vehicles. Apart from them, in the Military District of Lodz functioned also smaller units of the military engineer service and communication service. Despite many difficulties, all these services were in practice able to carry out their tasks, providing all military units in the military district necessary conditions for their functioning in peacetime. Majority of the units of all services, which were described in this article were stationed in Lodz and were disbanded in November 1946, together with the entire military district in Lodz.